CORRELATION OF ANKLE BRACHIAL INDEX AND BRACHIAL-ANKLE PULSE WAVE VELOCITY WITH FRAMINGHAM RISK SCORE AS CARDIOVASCULAR DISEASE RISK PREDICTOR - ADI TAMA NASUTION - NIM : 23215140 , TUTI
Abstract—Cardiovascular risk can be assessed either invasively or non-invasively. Invasive assessment of cardiovascular risk is based on traditional risk factors like gender, age, systolic blood pressure, status of hypertension treatment, status of smoking habit, cholesterol level, diabetes status, family health history, and hs-CRP level. Framingham Risk Score (FRS) is common invasive assessment to predict the 10-year risk of cardiovascular disease. Non-invasive assessment of cardiovascular risk is achieved by using baPWV and ABI parameters. baPWV, which is the indicator of brachial-femoral stiffness, including aorta, can be calculated by dividing travelled distance by travel time of wave between brachial and ankle point. Non-invasive ABI parameters as an independent systemic atherosclerotic indicator is determined by comparing the systolic blood pressure at the ankle with the highest systolic blood pressure between the two brachialis. This research is a cross sectional study aims to obtain the correlation between baPWVABI and their traditional risk factors. The traditional risk factors are determined by means of three methods: FRS Adult Treatment Panel 3 (FRS ATP3), FRS, and Reynolds Risks Score (RRS). The values of baPWV and ABI are measured using oscillometric signal of pressure sensor. This correlation is analyzed using Pearson Product Moment and Spearman’s. There are 78 contributing respondents in this research. The result showed that baPWV is the most significant in correlation with the traditional risk factors. The correlation between baPWV and FRS ATP 3, baPWV and FRS, also bPWV and RRS are 0.525 (P < 0.01), 0.579 (P< 0.01), dan 0.559 (P < 0.01), respectively. On the other hand, the correlation between ABI and FRS ATP III, ABI and FRS, also ABI and RRS were 0.456 (P < 0.01) 0.419 (P < 0.01) and 0.482 (P < 0.01), respectively. baPWV had positive correlation with age, blood pressure, and BMI such that baPWV increase with increasing age, blood pressure, and obesity level. The mean value of baPWV in men: 1069.9 (SD 178.05) cm/s, is higher than baPWV mean values in women: 991.71 (SD 205.15) cm/s. baPWV mean value in post-menopausal women: 1202.1 (SD 110.05) cm/s, is higher than baPWV mean value in pre-menopausal women: 906.24 (SD 235.79) cm/s.